2007
DOI: 10.1111/j.1540-8159.2007.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in End‐Stage Renal Disease

Abstract: End-stage renal disease (ESRD) is associated with increased cardiovascular morbidity and mortality. Recent studies indicate that atrial fibrillation (AF) is prevalent among ESRD patients while it adversely affects the clinical outcome. Despite these considerations, AF management in this population is problematic. Notably, most ESRD patients with AF are deprived of the benefits of anticoagulation therapy because of the fear of hemorrhagic complications. This article provides a concise and critical overview of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 57 publications
1
39
1
Order By: Relevance
“…31,32 Furthermore, whether through the predisposition to AF or as a marker of chronic LV diastolic impairment, recent evidence confirms an association between LA dilatation and increased mortality in ESRF patients with LV hypertrophy. [32][33][34] Our study would support the conclusion that changes in atrial dimension following AVF-creation may play a significant role in the promotion of atrial arrhythmia within the ESRF milieu.…”
supporting
confidence: 73%
“…31,32 Furthermore, whether through the predisposition to AF or as a marker of chronic LV diastolic impairment, recent evidence confirms an association between LA dilatation and increased mortality in ESRF patients with LV hypertrophy. [32][33][34] Our study would support the conclusion that changes in atrial dimension following AVF-creation may play a significant role in the promotion of atrial arrhythmia within the ESRF milieu.…”
supporting
confidence: 73%
“…The estimated prevalence of AF in these patients is reported to be in the range of 7.0–27.0% [8,9]. Ananthapanyasut et al [10] reported a 21.2% (n = 214) incidence of AF among 1,010 nondialysis CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Korantzopoulos P et al the incidence of AF in patients with end stage renal disease (ESRD) is between 1 and 4.1 per 100 patient-years 22 . Vazquez et al extended previous observations to report on the prevalence and incidence of AF in a cohort of patients who started dialysis at that group's center and who were followed for a mean period of 2 years.…”
Section: Resultsmentioning
confidence: 99%